2019
DOI: 10.3390/ijerph16081402
|View full text |Cite
|
Sign up to set email alerts
|

Can Work Engagement Be a Resource for Reducing Workaholism’s Undesirable Outcomes? A Multiple Mediating Model Including Moderated Mediation Analysis

Abstract: This study aimed to explore a possible process explaining the relationship between workaholism and sleep disorders, including two mediators: work–family conflict and emotional exhaustion. Moreover, since a possible buffering role of work engagement was recently proposed against the detrimental effects of workaholism, the aim was to examine the moderating role of work engagement in the relationship between workaholism and several outcomes such as work–family conflict, emotional exhaustion, and sleep disorders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 107 publications
1
16
0
1
Order By: Relevance
“…The first hypothesis of our study (H 1 ) was confirmed: the latent construct called work overload, reflectively measured by workload and techno overload, positively influenced behavioral stress during the COVID-19 health emergency. Results confirmed that both constructs, enclosed in a more general dimension, showed a positive and significant relationship with stress, which is in line with previous studies (La Torre et al, 2019;Scafuri Kovalchuk et al, 2019;Thulin et al, 2019); according to the JD-R model's perspective, these types of job demands have a direct and evident impact on the health impairment process, such as behavioral stress.…”
Section: Discussionsupporting
confidence: 90%
“…The first hypothesis of our study (H 1 ) was confirmed: the latent construct called work overload, reflectively measured by workload and techno overload, positively influenced behavioral stress during the COVID-19 health emergency. Results confirmed that both constructs, enclosed in a more general dimension, showed a positive and significant relationship with stress, which is in line with previous studies (La Torre et al, 2019;Scafuri Kovalchuk et al, 2019;Thulin et al, 2019); according to the JD-R model's perspective, these types of job demands have a direct and evident impact on the health impairment process, such as behavioral stress.…”
Section: Discussionsupporting
confidence: 90%
“…Studies consistently show that WA is associated with low sleep quality and sleep problems (see Griffiths et al, 2018). Recently, there has been a rapidly increasing number of studies aiming to explain the mechanisms by which WA affects sleep disturbance (Gillet, Morin, Sandrin, & Houle, 2018;Hancock et al, 2019;Reiner et al, 2019;Scafuri et al, 2019;Spagnoli, Balducci, Fabbri, Molinaro, & Barbato, 2019;Spagnoli, Balducci, Scafuri, Maiorano, & Buono, 2018). This is an especially appreciated effort since sleep is closely related to health and mortality (Gallicchio & Kalesan, 2009).…”
Section: Work Addiction Eating Disorders and Sleepmentioning
confidence: 99%
“…Work engagement is defined as an active, positive, work-related state of mind that is characterized by vigor, dedication, and absorption [31]. Engaged employees are full of energy and have abundant resources [32][33][34].…”
Section: Introductionmentioning
confidence: 99%